A graphite negative electrode material and its preparation method and application, lithium ion battery

By using supercritical fluid to peel off graphene and chitosan and composite them at high temperatures, a graphite anode material with a rich channel structure is constructed, which solves the problem of insufficient electrochemical performance of existing lithium-ion battery anode materials and significantly improves the performance of lithium-ion batteries. Rate and cycle performance.

CN117865144BActive Publication Date: 2025-01-24HUANENG CLEAN ENERGY RES INST +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410034214.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-09
Publication Date
2025-01-24
Estimated Expiration
2044-01-09

AI Technical Summary

Technical Problem

The electrochemical performance of existing lithium-ion battery anode materials needs to be improved and improved to meet the needs of high energy storage and fast charging and discharging.

Method used

Through the supercritical fluid peeling graphene and chitosan, the bonding, covering, and carbonization of the melting and melting of chitosan at high temperatures builds graphite negative materials with rich channel structures.

Benefits of technology

The preparation of graphite negative materials for multi -storage lithium -storage channels improves the conductivity, promotes lithium ion transmission, and improves the magnification and cycle performance of the lithium -ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117865144B_ABST
    Figure CN117865144B_ABST
Patent Text Reader

Abstract

The present invention discloses a graphite negative electrode material and a preparation method and application thereof, and a lithium ion battery. The preparation method of the graphite negative electrode material comprises the following steps: (1) dissolving chitosan in a solvent to obtain a chitosan solution; adding graphite and supercritical fluid exfoliated graphene to the chitosan solution for mixing to obtain a mixture; (2) drying the mixture, and then carbonizing it to obtain a graphite negative electrode material. In the present invention, the supercritical fluid exfoliated graphene is compounded with graphite through the bonding, coating and carbonization of chitosan in a molten state at high temperature to construct a channel-rich structure negative electrode material, thereby realizing the preparation of a graphite negative electrode material with multiple lithium storage channels, improving the conductivity of the graphite negative electrode material, promoting lithium ion transmission, and improving the rate performance and cycle performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a graphite negative electrode material, a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] The development of portable and telecommunication electronic devices requires efficient energy storage systems. Lithium-ion batteries (LIBs) are considered one of the most promising energy storage applications due to their high energy conversion and storage efficiency. Currently, lithium-ion batteries are growing and their applications are becoming more and more extensive. In current and future transportation tools, such as electric vehicles and the development of high-performance electronic products, various devices are increasingly demanding high-capacity lithium batteries.

[0003] In 2004, Novoselov et al. prepared graphene using an artificial exfoliation method, which triggered a worldwide research boom. Graphene is a two-dimensional material with a thickness of only one carbon atom (0.35nm). At room temperature, graphene transfers electrons faster than any other known conductor.

[0004] At present, the electrochemical performance of negative electrode materials is in urgent need of improvement and enhancement. Therefore, it is of great significance to study the modification of lithium-ion battery electrode materials and develop new lithium-ion battery negative electrode materials. Summary of the invention

[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems: At present, the electrochemical performance of negative electrode materials is in urgent need of improvement and enhancement. Therefore, it is of great significance to study the modification of lithium ion battery electrode materials and develop new lithium ion battery negative electrode materials.

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a graphite negative electrode material and a preparation method and application thereof, and a lithium-ion battery, wherein the graphene exfoliated by supercritical fluid is compounded with graphite through the bonding, coating and carbonization of chitosan in a molten state at high temperature to construct a channel-rich structure negative electrode material, realize the preparation of a graphite negative electrode material with multiple lithium storage channels, improve the conductivity of the graphite negative electrode material, promote lithium ion transmission, and improve the rate performance and cycle performance of the lithium-ion battery.

[0007] An embodiment of the present invention provides a method for preparing a graphite negative electrode material, comprising the following steps:

[0008] (1) dissolving chitosan in a solvent to obtain a chitosan solution; adding graphite and supercritical fluid exfoliated graphene to the chitosan solution and mixing them to obtain a mixture;

[0009] (2) The mixture is dried and then carbonized to obtain a graphite negative electrode material.

[0010] Advantages and technical effects of the method for preparing the graphite negative electrode material of the embodiment of the present invention: chitosan is preferably coated on the surface of graphite and supercritical fluid exfoliated graphene by mixing by a solution method, and the coating layer is complete, which is conducive to improving the comprehensive performance of the graphite negative electrode material. The supercritical fluid exfoliated graphene is compounded with graphite through the bonding, coating, carbonization and other effects of chitosan in a molten state at high temperature to construct a channel-rich structure negative electrode material, realize the preparation of graphite negative electrode materials with multiple lithium storage channels, improve the conductivity of graphite negative electrode materials, promote lithium ion transmission, and improve the rate performance and cycle performance of lithium-ion batteries.

[0011] In some embodiments, in step (1), the method for preparing supercritical fluid exfoliated graphene comprises: mixing graphite and supercritical CO 2 Mixing, fluid shearing, and then exhausting CO through pressure relief 2 , and supercritical fluid exfoliated graphene was obtained.

[0012] In some embodiments, the fluid shear temperature is 44-62°C;

[0013] And / or, the shear pressure of the fluid is 8.6-11.3 MPa;

[0014] And / or, the fluid shearing speed is 1600-2400 r / min;

[0015] And / or, the fluid shearing time is 15-60 minutes.

[0016] In some embodiments, in step (1), the graphite comprises natural flake graphite;

[0017] And / or, the particle size of the graphite is 70-100 μm;

[0018] And / or, the viscosity of the chitosan is 200-500 mPa·S;

[0019] And / or, the solvent is a non-oxidizing acid; preferably, the non-oxidizing acid includes at least one of hydrochloric acid, sulfuric acid, and citric acid;

[0020] And / or, the ratio of chitosan to solvent is 1-3 g: 200-300 mL.

[0021] In some embodiments, in step (1), the mass ratio of the graphite and supercritical fluid exfoliated graphene to the mass ratio of chitosan is 20:1 to 3;

[0022] And / or, in the graphite and the supercritical fluid exfoliated graphene, the mass percentage of the supercritical fluid exfoliated graphene is 0.01-10%.

[0023] In some embodiments, in step (2), the carbonization treatment adopts programmed temperature rise; the programmed temperature rise includes: heating to 800-900°C at a heating rate of 3-8°C / min, then heating to 1000-1200°C at a heating rate of 1-3°C / min, and keeping warm for 1-3h.

[0024] In some embodiments, in step (2), the particle size of the graphite negative electrode material is 10-70 μm.

[0025] The embodiment of the present invention provides a graphite negative electrode material, and the graphite negative electrode material is prepared by the preparation method described in the embodiment of the present invention. In the embodiment of the present invention, supercritical fluid exfoliated graphene is compounded with graphite through bonding, coating, carbonization and other effects of chitosan in a molten state at high temperature to construct a channel-rich structure negative electrode material, thereby realizing the preparation of a graphite negative electrode material with multiple lithium storage channels, improving the conductivity of the graphite negative electrode material, promoting lithium ion transmission, and improving the rate performance and cycle performance of lithium-ion batteries.

[0026] The embodiment of the present invention provides an application of a graphite negative electrode material, and the graphite negative electrode material is used in a lithium ion battery. In the embodiment of the present invention, all the advantages of the graphite negative electrode material are possessed, which will not be described in detail here.

[0027] The embodiment of the present invention provides a lithium ion battery, comprising the graphite negative electrode material according to the embodiment of the present invention. In the embodiment of the present invention, all the advantages of the graphite negative electrode material are possessed, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the SEM picture of the negative electrode material of comparative example 2 and embodiment 1.

[0029] Figure 2 It is the BET diagram of the negative electrode materials of the embodiment and the comparative example.

[0030] Figure 3 It is the pore size distribution diagram of the negative electrode materials of the embodiment and the comparative example. DETAILED DESCRIPTION

[0031] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0032] A method for preparing a graphite negative electrode material according to an embodiment of the present invention comprises the following steps:

[0033] (1) dissolving chitosan in a solvent to obtain a chitosan solution; adding graphite and supercritical fluid exfoliated graphene to the chitosan solution and mixing them to obtain a mixture;

[0034] (2) The mixture is dried and then carbonized to obtain a graphite negative electrode material.

[0035] The preparation method of the graphite negative electrode material of the embodiment of the present invention adopts a solution method to mix and coat chitosan on the surface of graphite and supercritical fluid exfoliated graphene, and the coating layer is complete, which is conducive to the improvement of the comprehensive performance of the graphite negative electrode material. The supercritical fluid exfoliated graphene is compounded with graphite through the bonding, coating, carbonization and other effects of chitosan in the molten state at high temperature to construct a channel-rich structure negative electrode material, realize the preparation of graphite negative electrode materials with multiple lithium storage channels, improve the conductivity of graphite negative electrode materials, promote lithium ion transmission, and improve the rate performance and cycle performance of lithium ion batteries.

[0036] In some embodiments, in step (1), the method for preparing supercritical fluid exfoliated graphene comprises: mixing graphite and supercritical CO 2 Mixing, fluid shearing, and then exhausting CO through pressure relief 2 , obtaining supercritical fluid exfoliated graphene;

[0037] Preferably, the graphite is first pre-treated by ball milling to obtain graphite powder, and then the pre-treated graphite powder is added to an autoclave and introduced into a supercritical CO 2 Mixing; preferably, the ball milling uses a ball mill;

[0038] Preferably, the shearing temperature of the fluid is 44-62°C, specifically, for example, 44°C, 50°C, 54°C, 60°C, 62°C; and / or the shearing pressure of the fluid is 8.6-11.3MPa, specifically, for example, 8.6MPa, 9MPa, 9.8MPa, 10MPa, 11MPa, 11.3MPa; and / or the shearing speed of the fluid is 1600-2400r / min, specifically, for example, 1600r / min, 2000r / min, 2100r / min, 2400r / min; and / or the shearing time of the fluid is 15-60min, specifically, for example, 15min, 30min, 35min, 45min, 60min.

[0039] In the embodiment of the present invention, a method for preparing graphene by supercritical fluid exfoliation is preferred, using supercritical CO 2 Excellent diffusivity, permeability and solubility, low viscosity and surface tension, are conducive to intercalation into the graphite interlayer; and high-speed rotation makes CO 2The strong shear force generated between the fluids not only strengthens the diffusion process of molecules, but also promotes the destruction of the van der Waals force between the graphite layers by molecules. 2 Rapid pressure relief and expansion, exfoliation of graphite to prepare supercritical fluid exfoliated graphene. Compared with other methods of introducing strong acid or strong base to widen the graphite interlayer distance to achieve the effect of rapid embedding of lithium ions into graphite, this method not only greatly reduces the cost, but also does not produce a large amount of waste acid, and is environmentally friendly. Compared with other graphenes, supercritical fluid exfoliation of graphene is conducive to further improving the fast charging performance, rate performance and cycle performance of negative electrode materials.

[0040] In the embodiment of the present invention, the graphite raw material is first pre-treated by ball milling to reduce the particle size and number of layers of the raw material, so that supercritical exfoliation is easier to perform. In a supercritical state system, temperature, pressure, fluid shear rate and time will have a great influence on graphene. By optimizing temperature, pressure, etc., a supercritical fluid suitable for negative electrode materials is obtained to exfoliate graphene, which can accelerate the rapid transfer of electrons, thereby improving the rate performance of negative electrode materials.

[0041] In some embodiments, graphite is pre-treated by ball milling to obtain graphite powder, and then the pre-treated graphite powder is added to an autoclave, packaged, and the temperature of the autoclave is set. When the temperature reaches the set value, CO is introduced. 2 Gas, start the pressure pump, and when the pressure reaches the preset value, close the valve to stop the CO 2 Gas, fluid shear, and then discharge CO through pressure relief 2 , obtaining supercritical fluid exfoliated graphene; preferably, the ball milling adopts a ball mill; preferably, the fluid shearing adopts magnetic stirring.

[0042] In some embodiments, in step (1), the graphite includes natural flake graphite; and / or the particle size of the graphite is 70-100 μm, specifically, for example, 70 μm, 80 μm, 90 μm, 100 μm.

[0043] In some embodiments, in step (1), the viscosity of the chitosan is 200-500 mPa·S, specifically, for example, 200 mPa·S, 300 mPa·S, 400 mPa·S, 500 mPa·S; and / or the particle size of the chitosan is 80-100 μm; and / or the solvent is a non-oxidizing acid; preferably, the non-oxidizing acid comprises at least one of hydrochloric acid, sulfuric acid, and citric acid; preferably, the concentration of the non-oxidizing acid is 0.5-2 mol / l; and / or the ratio of chitosan to solvent is 1-3 g:200-300 mL, specifically, for example, 1-3 g (1 g, 1.5 g, 2 g, 3 g):200-300 mL (200 mL, 250 mL, 300 mL).

[0044] In some embodiments, in the step (1), the mass ratio of the graphite and supercritical fluid exfoliated graphene to the mass ratio of chitosan is 20:1-3, specifically, for example, 20:1, 20:1.5, 20:1.8, 20:2, 20:3; and / or, in the graphite and supercritical fluid exfoliated graphene, the mass percentage of supercritical fluid exfoliated graphene is 0.01-10%, specifically, for example, 0.01%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. In the embodiment of the present invention, the amount of graphite, supercritical fluid exfoliated graphene, and chitosan is preferably selected, which is conducive to further improving the rate performance and cycle performance of the negative electrode material. When the amount of supercritical fluid exfoliated graphene added is relatively large or the amount of chitosan used is relatively small, the material will find it difficult to form a complete carbon coating structure due to the large specific surface area of ​​supercritical fluid exfoliated graphene; when the amount of supercritical fluid exfoliated graphene added is relatively small or the amount of chitosan used is relatively large, although the coating state is good, the improvement in the conductivity of the material is not obvious.

[0045] In some embodiments, in step (2), the drying is performed by rotary evaporation. In the embodiment of the present invention, the solvent is removed by rotary evaporation.

[0046] In some embodiments, in step (2), the carbonization process adopts programmed temperature rise, and the programmed temperature rise includes: heating to 800-900°C (specifically, for example, 800°C, 850°C, 900°C) at a heating rate of 3-8°C / min (specifically, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min), and then heating to 800-900°C (specifically, for example, 800°C, 850°C, 900°C) at a heating rate of 1-3°C / min (specifically, for example, 1°C / min). min, 2 ° C / min, 3 ° C / min) at a heating rate of 1000-1200 ° C (specifically, for example, 1000 ° C, 1100 ° C, 1150 ° C, 1200 ° C), and keep warm for 1-3h (specifically, for example, 1h, 2h, 3h); preferably, after keeping warm, the temperature is lowered to 20-30 ° C, specifically, for example, 20 ° C, 25 ° C, 30 ° C; preferably, the temperature is raised from room temperature; preferably, the atmosphere of the carbonization treatment is Ar atmosphere.

[0047] In the embodiment of the present invention, the carbonization process can affect the coating degree of the coating material. By optimizing the carbonization process, such as the carbonization temperature and time, it is beneficial to obtain an ordered coating layer, thereby affecting the infiltration effect of the electrolyte in the battery on the graphite negative electrode material, affecting the rate of lithium ion embedding into the negative electrode material, and further improving the fast charging performance of the battery. When the carbonization temperature is too low, the defect degree of the carbon coating layer is relatively high, which is not conducive to improving the conductivity of the material; when the carbonization temperature is too high, the defect degree in the material is relatively low. Although the conductivity of the graphite negative electrode material is greatly improved, the lithium ion storage sites are reduced and the lithium embedding capacity is reduced.

[0048] In some embodiments, the carbonization process further includes grinding and screening.

[0049] In some embodiments, in step (2), the particle size of the graphite negative electrode material is 10-70 μm, specifically, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm.

[0050] A graphite negative electrode material according to an embodiment of the present invention is prepared by the preparation method according to an embodiment of the present invention. In the embodiment of the present invention, supercritical fluid exfoliated graphene is compounded with graphite through bonding, coating, carbonization, etc. of chitosan in a molten state at high temperature to construct a channel-rich structure negative electrode material, thereby realizing the preparation of a graphite negative electrode material with multiple lithium storage channels, improving the conductivity of the graphite negative electrode material, promoting lithium ion transmission, and improving the rate performance and cycle performance of lithium-ion batteries.

[0051] An application of a graphite negative electrode material in an embodiment of the present invention is used in a lithium-ion battery. In the embodiment of the present invention, all the advantages of the graphite negative electrode material are possessed, which will not be described in detail here.

[0052] A lithium ion battery according to an embodiment of the present invention comprises the graphite negative electrode material according to the embodiment of the present invention. In the embodiment of the present invention, all the advantages of the graphite negative electrode material are possessed, which will not be described in detail here.

[0053] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0054] Example 1

[0055] The method for preparing a graphite negative electrode material comprises the following steps:

[0056] (1) Graphite is pre-milled to obtain graphite powder, and then the pre-treated graphite powder is added to an autoclave and supercritical CO is introduced. 2Mixing and fluid shearing are performed at a fluid shearing temperature of 54°C, a fluid shearing pressure of 9.8 MPa, a fluid shearing speed of 2100 r / min, and a fluid shearing time of 35 min, and then the CO is discharged through pressure relief. 2 , obtaining supercritical fluid exfoliated graphene;

[0057] (2) 1.5 g of chitosan (viscosity 300 mPa·S) was placed in 250 ml of 1 mol / l hydrochloric acid and fully dissolved to obtain a chitosan solution; 19 g of graphite and 1 g of supercritical fluid exfoliated graphene (5%) were then added thereto, and the mixture was fully stirred to obtain a mixture; the hydrochloric acid solvent in the mixture was removed by rotary evaporation, and then carbonization treatment was performed. The carbonization treatment was performed by programmed temperature increase: from room temperature to 900°C at 5°C / min, and then to 1100°C at 2°C / min, and kept warm for 2 hours to obtain a graphite negative electrode material.

[0058] Material Characterization:

[0059] The graphite raw material and the graphite negative electrode material of Example 1 were characterized by SEM.

[0060] Lithium battery performance test:

[0061] 1) The negative electrode material, acetylene black and PVDF were mixed in a mass ratio of 92:3:5, an appropriate amount of NMP was added, stirred at room temperature for 6 hours, coated on a copper foil, dried at 120°C for 12 hours, and pressed into a negative electrode sheet with a diameter of 13 mm using a tablet press;

[0062] 2) Assemble CR2032 button cells in the glove box.

[0063] 3) Carry out charge and discharge tests in the Xinwei battery testing system to test the battery's rate performance and cycle performance.

[0064] Example 2

[0065] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), the amount of graphite used is 19.6 g, and the amount of supercritical fluid exfoliated graphene used is 0.4 g (2%).

[0066] Example 3

[0067] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), the amount of graphite used is 18.4 g, and the amount of supercritical fluid exfoliated graphene used is 1.6 g (8%).

[0068] Comparative Example 1

[0069] The performance test method is the same as that of Example 1, except that the negative electrode material uses a commercial graphite negative electrode.

[0070] Comparative Example 2

[0071] The performance test method is the same as that of Example 1, except that the negative electrode material is graphite.

[0072] Comparative Example 3

[0073] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), the amount of graphite used is 20.0 g, and no supercritical fluid is added to exfoliate the graphene.

[0074] Comparative Example 4

[0075] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), the supercritical fluid exfoliated graphene is replaced by commercial graphene (purchased from Pioneer Nano).

[0076] Comparative Example 5

[0077] The preparation method and performance testing method are the same as those of Example 1, except that in step (2), the supercritical exfoliated graphene is replaced by few-layer graphene.

[0078] Comparative Example 6

[0079] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), the supercritical fluid exfoliated graphene is replaced by graphene oxide.

[0080] Comparative Example 7

[0081] The preparation method and performance testing method are the same as those of Example 1, except that in step (2), the supercritical fluid exfoliated graphene is replaced by hydrogenated graphene.

[0082] Comparative Example 8

[0083] The preparation method and performance test method are the same as those in Example 1, except that in step (2), no chitosan is added, that is, 19 g of graphite and 1 g of supercritical fluid exfoliated graphene (5%) are fully stirred to obtain a graphite negative electrode material.

[0084] Comparative Example 9

[0085] The preparation method and performance test method are the same as those in Example 1, except that in step (2), chitosan is replaced by asphalt, that is, 1.5 g of asphalt is placed in 250 ml of 1 mol / l hydrochloric acid and mixed thoroughly to obtain a mixed solution.

[0086] Comparative Example 10

[0087] The preparation method and performance test method are the same as those in Example 1, except that in step (2), chitosan is replaced by epoxy resin, that is, 1.5 g of epoxy resin is placed in 250 ml of 1 mol / l hydrochloric acid and mixed thoroughly to obtain a mixed solution.

[0088] Comparative Example 11

[0089] The preparation method and performance testing method are the same as those in Example 1, except that in step (2), chitosan is replaced by glucose.

[0090] Comparative Example 12

[0091] The preparation method and performance testing method are the same as those of Example 1, except that in step (2), the carbonization temperature is 1300°C.

[0092] That is, the programmed temperature rise program is: from room temperature to 900°C at 5°C / min, then to 1300°C at 2°C / min, and keep warm for 2h.

[0093] Comparative Example 13

[0094] The preparation method and performance test method are the same as those in Example 1, except that in step (2), the temperature program is: heating from room temperature to 1100° C. at 5° C. / min and keeping the temperature for 2 h.

[0095] Table 1

[0096]

[0097] The conductivity data of the supercritical fluid exfoliated graphene in Example 1 and the graphene in Comparative Examples 4-7 are shown in Table 1. Among them, the conductivity of the supercritical fluid exfoliated graphene in Example 1 is 4.5×10 6 S / m, which is much higher than the conductivity of other graphene.

[0098] Table 2 Rate reversible capacity (mAh / g)

[0099]

[0100] It can be seen from Table 2 that the introduction of supercritical fluid exfoliated graphene in Examples 1-3 makes the rate performance of the graphite negative electrode material better than the commercial graphite negative electrode material, graphite and the negative electrode material without adding supercritical fluid exfoliated graphene in Comparative Examples 1-3, indicating that supercritical fluid exfoliated graphene improves the rate performance of the graphite negative electrode material, and the performance is better than that of the commercial graphite negative electrode.

[0101] The negative electrode material with 5% graphene addition in Example 1 still has 60.1 mAh g at 3C rate. -1 , far exceeding the commercial graphite negative electrode, which shows that the introduction of supercritical fluid exfoliated graphene increases the multi-porous structure and promotes the transmission of lithium ions; in addition, the high conductivity of supercritical fluid exfoliated graphene is conducive to improving the rate performance and fast charging performance of graphite negative electrode materials. In Example 2, the addition amount of supercritical fluid exfoliated graphene is 2%, and there is 45.9mAh g at 3C rate. -1 The capacity is 200 ℃ and 800 ℃, but it is lower than the performance of 5% addition in Example 1. This is because when the addition amount of supercritical fluid exfoliated graphene is lower than that in Example 1, it is not conducive to fully exerting the high conductivity characteristics of supercritical fluid exfoliated graphene, resulting in relatively poor performance of the negative electrode material at high rate; when the addition amount of supercritical fluid exfoliated graphene is 8% in Example 3, the performance at 3C rate is slightly higher than 2%, but lower than 5%. This is because although the amount of supercritical fluid exfoliated graphene is increased in Example 3, due to the relatively large addition amount of supercritical fluid exfoliated graphene, the chitosan coating is relatively incomplete, and the supercritical fluid exfoliated graphene cannot be fully and tightly attached to the graphite, which is not conducive to high conductivity, thereby affecting the high rate performance of the graphite negative electrode material.

[0102] By comparing Example 1 with Comparative Examples 4-7, it can be seen that the graphite negative electrode material using supercritical fluid to exfoliate graphene in Example 1 has a significantly improved capacity at high rates compared to negative electrode materials using other graphenes.

[0103] By comparing Example 1 with Comparative Examples 8-11, it can be seen that the graphite negative electrode material using chitosan in Example 1 has the best rate performance compared to other coating materials. This is not only due to the ultra-high conductivity of graphene exfoliated by supercritical fluid, but also due to the unique characteristics of chitosan as a precursor. After high-temperature carbonization at 1100°C, the graphite material coated with chitosan forms a regular core-shell structure, which effectively reduces the lithium ion diffusion resistance and greatly improves the diffusion rate of lithium ions in the electrolyte.

[0104] By comparing Example 1 with Comparative Examples 12-13, it can be seen that optimizing the temperature and heating process of the carbonization treatment is beneficial to further improve the rate performance of the graphite negative electrode material.

[0105] Table 3 Cyclic reversible capacity (0.1C, mAh / g)

[0106]

[0107]

[0108] It can be seen from Table 3 that the long cycle performance of graphite negative electrode materials coated with different coating materials is different. Due to the unique structure of chitosan after carbonization treatment, the electrolyte is completely infiltrated and a stable SEI film is formed on the surface of the material, so that Example 1 has excellent long cycle performance. After 2000 cycles, the reversible capacity still reaches 329.4 mAh / g.

[0109] Figure 1 It is the SEM picture of the graphite in comparative example 2 and the graphite negative electrode material in Example 1. It can be seen from the figure that the graphite negative electrode material modified by chitosan and supercritical fluid exfoliation of graphene in Example 1 is smooth, and the graphene forms a complete coating layer.

[0110] Figure 2 and Figure 3 The BET graph and pore size distribution graph are shown respectively. Among them, the specific surface area of ​​the commercial graphite negative electrode material in Comparative Example 1 is 1.04 m 2 / g, the specific surface area of ​​the graphite in Comparative Example 2 is 0.54m 2 / g, the specific surface area of ​​the graphite negative electrode material of Example 1 is 4.67m 2 / g, the specific surface area of ​​the graphite negative electrode material of Example 2 is 3.12m 2 / g, the specific surface area of ​​the graphite negative electrode material of Example 3 is 5.68m 2 / g, after the introduction of supercritical fluid to exfoliate graphene in the embodiment, the specific surface area of ​​the graphite negative electrode material increases, which increases the contact area between the material and the electrolyte, which is beneficial to the embedding and extraction of lithium ions. In addition, it can be seen from the pore size distribution diagram that the pore richness and pore volume of the graphite negative electrode material in the embodiment increase, indicating that the introduction of supercritical fluid to exfoliate graphene increases the multi-porous structure of the material, providing a richer path for the embedding and extraction of lithium ions, which is beneficial to fast charging performance.

[0111] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0112] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a graphite negative electrode material, characterized in that: The following steps are involved: (1) dissolving chitosan in a solvent to obtain a chitosan solution; adding graphite and supercritical fluid exfoliated graphene to the chitosan solution and mixing them to obtain a mixture; (2) drying the mixture and then carbonizing it to obtain a graphite negative electrode material; In the step (1), the preparation method of supercritical fluid exfoliated graphene comprises: mixing graphite and supercritical CO2, performing fluid shearing, and then discharging CO2 by pressure relief to obtain supercritical fluid exfoliated graphene; the fluid shearing speed is 1600-2400r / min; In the step (2), the carbonization treatment adopts programmed temperature rise; the programmed temperature rise includes: heating to 800-900°C at a heating rate of 3-8°C / min, then heating to 1000-1200°C at a heating rate of 1-3°C / min, and keeping warm for 1-3h.

2. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The fluid shear temperature is 44-62°C; And / or, the shear pressure of the fluid is 8.6-11.3 MPa; And / or, the fluid shearing time is 15-60 minutes.

3. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In the step (1), the graphite comprises natural flake graphite; And / or, the particle size of the graphite is 70-100 μm; And / or, the viscosity of the chitosan is 200-500 mPa·S; and / or, the solvent is a non-oxidizing acid; And / or, the ratio of chitosan to solvent is 1-3 g: 200-300 mL.

4. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The non-oxidizing acid includes at least one of hydrochloric acid, sulfuric acid and citric acid.

5. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In the step (1), the mass ratio of the graphite and the supercritical fluid exfoliated graphene to the mass ratio of chitosan is 20:1 to 3; And / or, in the graphite and the supercritical fluid exfoliated graphene, the mass percentage of the supercritical fluid exfoliated graphene is 0.01-10%.

6. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In the step (2), the particle size of the graphite negative electrode material is 10-70 μm.

7. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the preparation method described in any one of claims 1 to 6.

8. An application of the graphite negative electrode material according to claim 7, characterized in that: The graphite negative electrode material is used in lithium ion batteries.

9. A lithium ion battery, characterized in that: Comprising the graphite negative electrode material as described in claim 8.

Citation Information

Patent Citations

  • Method for preparing large-scale graphene through supercritical carbon dioxide exfoliation

    CN102515155A

  • Graphite negative electrode material for lithium ion battery and preparation method of graphite negative electrode material

    CN104124431A

  • Preparation method of graphene-dopedand carbon-coated modified graphite anode material

    CN104934603A

  • Method for preparing graphene by supercritical fluid steam explosion method

    CN106927454A

  • Graphene coated artificial graphite negative electrode material preparation method

    CN107507963A